Perancangan Dan Pengukuran Kinerja Sumber Daya Manusia Menggunakan Metode Human Resources Scorecard dan Analytical Hierarchy Process (AHP) (Studi Kasus : PT. Rajawali Malik Jaya Pekanbaru) - Ari Andriyas Puji; Faradila Ananda Yul; Nova Meirizha; Denny Astrie Anggraini; Satriadi Satriadi (Research Center University of Pahlawan Tuanku Tambusai, 2022)
Performance appraisal is an important process in human resources, because the results of the performance appraisal will measure the competence, work behavior and work results of employees within a certain period of time as a basis for consideration in considering decisions in the field of human resources. Employee performance at PT. Rajawali Malik Jaya to complete 1 document takes a long time. From the problems found, the occurrence of long data processing makes work pile up so that employees are tired of processing data all at once. Therefore, to overcome and find out these problems, it is necessary to use the Human Resources Scorecard and Analytical Hierarchy Process methods to measure employee performance. Human Resources Scorecard analysis was obtained using 4 perspectives, namely financial perspective, consumer perspective, internal business perspective and growth and learning perspective, while the AHP analysis consisted of 4 criteria and 4 sub criteria. From the weighting results obtained, it is known that the smallest weight on the financial perspective is 0.13, the consumer perspective is 0.22, the growth and learning perspective is 0.20 and the internal business perspective is the largest weighted value, which is 0.40.